2012
DOI: 10.1128/jvi.00404-11
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Roles of cis -Acting RNA Elements in Tombusvirus Replicase Assembly In Vitro

Abstract: In addition to its central role as a template for replication and translation, the viral plus-strand RNA genome also has nontemplate functions, such as recruitment to the site of replication and assembly of the viral replicase, activities that are mediated by cis-acting RNA elements within viral genomes. Two noncontiguous RNA elements, RII(؉)-SL (located internally in the tombusvirus genome) and RIV (located at the 3=-terminus), are involved in template recruitment into replication and replicase assembly; howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 44 publications
2
50
0
Order By: Relevance
“…For example, cis-acting RNA elements located on the plus strand, such as the internal p33 recognition element (p33RE), the 3=-proximal silencer element, and the 3=-terminal minus-strand initiation promoter (gPR), consist of secondary structures needed for function, but these hairpin structures are unlikely to exist and are not functional when they are part of dsRNA structures (32,33,(36)(37)(38). Thus, masking of cis-acting elements located on the plus strand through the formation of dsRNA structures prevents competition between (ϩ)-and (Ϫ)RNAs for the replicase, and it allows the tombusvirus replicase become committed to plus-strand synthesis at later time points.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cis-acting RNA elements located on the plus strand, such as the internal p33 recognition element (p33RE), the 3=-proximal silencer element, and the 3=-terminal minus-strand initiation promoter (gPR), consist of secondary structures needed for function, but these hairpin structures are unlikely to exist and are not functional when they are part of dsRNA structures (32,33,(36)(37)(38). Thus, masking of cis-acting elements located on the plus strand through the formation of dsRNA structures prevents competition between (ϩ)-and (Ϫ)RNAs for the replicase, and it allows the tombusvirus replicase become committed to plus-strand synthesis at later time points.…”
Section: Discussionmentioning
confidence: 99%
“…Such cell-free viral RNA replication systems enable the biochemical analysis of replication processes and have been used to analyze how the replication complex is formed (33)(34)(35)(36)(37)(38)(39)(40). Using this in vitro system, we previously demonstrated that the Tm-1 protein inhibits ToMV RNA replication when added before, but not after, the ToMV replication complex is formed on membranes (28).…”
mentioning
confidence: 99%
“…and activation of the polymerase function of the replication protein (102,121). The specific recognition of p33RE is performed by arginines within the RPR motif in p33/p92 pol (122,123).…”
Section: Discussionmentioning
confidence: 99%
“…4D, construct p36⌬RPR). The RPR motif in replication proteins is required for specific viral (ϩ)RNA recruitment and replicase assembly, and it also binds to Cpr7p Cyp40-like cyclophilin (41,(102)(103)(104). Interestingly, the same RPR-containing region in p36 replication protein could bind to both the TPR1 and TPR2 sequences in Sti1p (Fig.…”
Section: The Binding Of Sti1p Involves Different Regions In Cirv P36mentioning
confidence: 99%